Empty Promises or Justiciable Rights: The Extraterritorial Reach of Economic, Social and Cultural Rights in the Context of Unilateral Sanctions - Paula Mosquera Marquez (Groningen Journal of International Law)
This paper examines the extraterritorial obligations of States under the ICESCR concerning the effects of their unilateral sectoral sanctions and the implications for human rights. It highlights that unilateral sectoral sanctions, while claimed to be targeted and accompanied by humanitarian exemptions, still negatively affect the economic and social rights of the people in the sanctioned State. This paper analyses the US and EU sanctions on Iran, Venezuela, and Syria, demonstrating how these sanctions impact the population of the sanctioned State. The present paper analyses the problematic nature hereof, especially since there is an absence of justiciable obligations under the ICESCR regarding the effects of unilateral sectoral sanctions on the population of the sanctioned State. Furthermore, this paper shows an incongruity between the theoretical framework of humanitarian exemptions and their practical implementation, which further exacerbates the impact of these sanctions on the population of a sanctioned State. Moreover, this paper offers insights into the legitimacy challenges posed by unilateral sanctions, given their actual humanitarian impact. It underscores the pressing need for countries to exercise restraint when imposing such sanctions and, more crucially, to reassess the implementation of humanitarian exemptions critically.